ANALYSIS OF SUCCESS FACTORS IMPLEMENTATION OF STATE CIVIL APPARATUS MANAGEMENT INFORMATION SYSTEM - Arsyanur, Mustika Retno; Suroso, Arif Imam; Sukmawati, Anggraini (Jurnal Aplikasi Manajemen, 2019)
The State Civil Apparatus Management Information System, commonly called as SIM ASN, is used to manage staff data that contains all information about the State Civil Apparatus at the Ministry of Agriculture. This study aims to analyze the factors that influence the success of SIM ASN, in accordance with DeLone and McLean's information system success model (2003). Specifically, the purpose of this study is to analyze the effect of information quality,system quality, and service quality on use and user satisfaction. Analyze the effect of the use on user satisfactionand analyze the use and user satisfaction on net benefits. The respondents involved in this study are 142 users of the SIM ASN.This study was analyzed using Structural Equation Modeling (SEM). The results showed that information quality, system quality, and service quality had a significant effect on user satisfaction, but only service quality had a significant effect on use;use does not have a significant effect on user satisfaction; use and user satisfaction have a significant effect on net benefits. By looking at the results, it can be concluded that the DeLone and McLean (2003) models were confirmed to be used in assessing the success of SIM ASN at the Ministry of Agriculture. Suggestion for further research is to develop a net benefit variable that is not only assessed on individuals but also benefits at the organizational level and needs research on the user competency model to find out competency standards for users of management information systems.